Application of Screen-Printed Taste Sensor for Quality Control Of Milk Freshness. - Sim, M.Y.M; Shya, T.J.; Ahmad, M.N.; Shakaff, A.Y.; Othman, Prof.Madya Abdul Rahman; Hitam, M.S. (2003)
A disposable taste sensor fabricate using screen-printing technology was developed to test various types of commercial milk products.